Effect of Storage Time and Temperature on Drinking Water Characteristics - Novi Fitria; Muammar Qadafi; Risma Pradina Kusuma; Wisnu Prayogo; Laili Fitria (Journal of Community Based Environmental Engineering and Management, 2023)
Filter membrane technology is known to remove turbidity, colour and microorganisms in water. However, the stability of these parameters during storage is still being determined. This research was conducted to determine changes in pH, turbidity, and total coliform of water treated using membrane filter technology and stored at room temperature and in the refrigerator. Water stored at room temperature increases the pH more easily during storage time. On the other hand, there was no significant difference between changes in the turbidity value of water stored at room temperature and in the refrigerator. Closed storage at room temperature and refrigerators can also protect water from the growth of total coliform. Water treated using membrane filter technology is proven to be stored at room temperature or in the refrigerator without experiencing significant changes in pH, turbidity, and total coliform.